TEKNIK MONOLOG INTERNAL DALAM FILM ANIMASI 2D “BAD HAIR DAY” - Dionisius Miki Pratama; Harthoko Tanto; Agnes Karina Pritha Atmani (Institut Seni Indonesia Yogyakarta, 2019)
The animated film Bad Hair Day tells the story of a girl who became a victim of bullying because she has a different physical form than her other friends. Bullying is an act of violence, oppression, or intimidation. In this film, Jane who has long, messy hair like a bush becomes a bully victim by her friends, so she feels depressed and sad. The turning point in this film is shown in a moment where the character Jane rediscovers something that has long been lost from her life: friendship. The intangible interconnected friendship that motivates him in the face of abuse carried out by his friends. The storytelling technique chosen is an internal monologue technique. Internal monologue is the technique of delivering stories whose source of sound comes from the thoughts or feelings of the character Jane in the film. Internal monologue technique will help the audience to better understand the feelings experienced by the main character in this film.